Self-assembly study of nanometric spheres from polyoxometalate-phenylalanine hybrids, an experimental and theoretical approach. Issue 18 (16th April 2018) - Nikoloudakis, Emmanouil; Karikis, Kostas; Laurans, Maxime; Kokotidou, Chrysoula; Solé-Daura, Albert; Carbó, Jorge J.; Charisiadis, Asterios; Charalambidis, Georgios; Izzet, Guillaume; Mitraki, Anna; Douvas, Antonios M.; Poblet, Josep M.; et al.
Abstract : Polyoxometalate-amino acid hybrids (POM-F andPOM-FF ) self-assemble into spherical architectures with high reproducibility in several "good–bad" solvent mixtures. Abstract : Herein, we report on the study of supramolecular assemblies based on polyoxometalates (POMs) upon their modification with amino acids. Two POM-amino acid hybrids were synthesized by coupling a functionalized Keggin type polyoxoanion [PW11 O39 Sn(C6 H4 )C}C(C6 H4 )COOH] 4− with carboxyl-protected (methyl-ester) phenylalanine or diphenylalanine peptides. Surprisingly, all compounds, including the initial POM, formed supramolecular nanospheres in different solvent mixtures, which were examined by scanning electron microscopy (SEM). Molecular dynamics (MD) simulations for the POM-amino acid species revealed that the hydrophobic forces are mainly responsible for the initial aggregation into incipient micelle type structures, in which the organic arms are buried inside the aggregate while POM polar heads are more exposed to the solvent with tetrabutyl-ammonium counter cations acting as linkers.